2006
DOI: 10.1002/anie.200600750
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalently Bonded Rotaxanes Cross‐Linked by Imine Bonds between the Axle and Ring: Inverse Temperature Dependence of Subunit Mobility

Abstract: Establishing methods to control submolecular movements of rotaxane components is a prerequisite for the development of artificial devices that function through translational and rotational motion at the molecular level. During the last decade, many systems capable of controlling interactions among components through external stimuli, such as metal binding, change in pH value, electrochemistry, light, or temperature, have been developed to realize on/off switching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…17 Having the tetra-bromo derivative 16 in hand, it was treated with various AMCs (Fig. 3) to assemble the corresponding di-bromo building blocks in a single step.…”
Section: Resultsmentioning
confidence: 99%
“…17 Having the tetra-bromo derivative 16 in hand, it was treated with various AMCs (Fig. 3) to assemble the corresponding di-bromo building blocks in a single step.…”
Section: Resultsmentioning
confidence: 99%
“…Chemicals were used as received from Alfa Aesar and/or Aldrich. [FcC(O)Cl],71 1,3,5‐tris(bromomethyl)‐2,4,6‐trimethylbenzene,72 1,2,4,5‐tetrakis(bromomethyl)benzene,73 Li[ESiMe 3 ]60 and Na[ESiMe 3 ]61 (E=S, Se) were synthesized according to literature procedures. 1,4‐bis(bromomethyl)‐2,3,5,6‐tetramethylbenzene was prepared according to similar procedure for 1,3,5‐tris(bromomethyl)‐2,4,6‐trimethylbenzene 72 .…”
Section: Methodsmentioning
confidence: 99%
“…Kawai, Umehara, Fujiwara, Tsuji, and Suzuki [98] showed that a bis-imine rotaxane (Fig. 9c3) composed of a macrocycle with two amino groups (Fig.…”
Section: Controlling the Position Of Macrocycles In [2]rotaxanesmentioning
confidence: 99%